Pretreatment by composting increased the utilization proportion of pig manure biogas digestate and improved the seedling substrate quality. (15th June 2021) - Chang, Ruixue; Guo, Qiuyue; Pandey, Pramod; Li, Yanming; Chen, Qing; Sun, Ying
Highlights: Composting increased the proportion of pig manure digestate in seedling substrate. Composting stabilize the physiochemical properties of pig manure digestate. Perlite and sawdust improve the physiochemical properties of PMBD in composting. Both PMBD and CPMBD improved plant growth performance, especially CPMBD. Tomato was more sensitive than Lettuce to the seedling substrate properties. Abstract: Anaerobic digestion of organic residues has the potential to significantly contribute to a shift from fossil to renewable energy, while the remaining biogas digestate need to be treated or used for a second time. In this study, the pig manure biogas digestate (PMBD) was evaluated as a potential part of seedling substrates and composting was considered a pretreating method to improve its characters. Composting was carried out firstly in a forced aeration composting system (100 L), in which perlite and sawdust were used as additives in different proportions separately or together. Based on the comparison of the physicochemical characters of different seedling substrates formulas mixed with PMBD or pig manure biogas digestate pretreated by composting (CPMBD), selected seedling substrates were analyzed by bioassay experiment. The results showed that pretreatment by composting and the additives (perlite and sawdust) used in composting decreased the pH value of PMBD and make it suitable for seedling substrates, especially composted with perlite and sawdust. Both PMBD and CPMBD with low proportion in the substrates improved plant growth of lettuce and tomato, while CPMBD was better than PMBD. However, when the proportions of PMBD was increased more than 20% and CPMBD was increased more than 40%, plant growth inhibition was observed. Tomato was more sensitive than lettuce to the physicochemical characters of the substrate. In summary, PMBD pretreated by composting not only increases the uses of digestate, but also enhances plant growth and hence yield.